National External Quality Assurance Scheme For Hiv Testing Using Dried Blood Spot: A Feasibility Study - Thapa, B; Koirala, S; Upadhaya, BP; Mahat, K; Malla, S; Shakya, G (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Introduction: Dried Blood Spot (DBS) for National External Quality Assurance Scheme (NEQAS) is becoming popular in resource limited and geographically constrained settings. The feasibility of using DBS for EQAS for HIV testing in Nepal is studied. Methodology: National Public Health Laboratory (NPHL) and fi ve Voluntary Counseling and Testing Centers (VCT) located at the Mid-Western and Central region of Nepal were chosen as the organizing and participating laboratories, respectively. HIV tests were performed on 35 samples using rapid test kits following the National algorithm. Two sets of samples were blotted on a DBS card, dried, packed, stored and posted to NPHL using normal postal delivery. The eluted DBS were tested by rapid test and ELISA and results were compared. Results: All DBS cards were received in a good condition. The rapid test result obtained at VCT and NPHL was 100% concordant. By ELISA, 32 (91.4%) and 3 (8.6%) samples were concordant and discordant, respectively. The sensitivity and specifi city of the rapid test were 88.9% and 94.0%, respectively. The DBS was stable with mean transportation time of 2.25 days and storage time of one month. Conclusion: DBS is an easy, simple, cost effective and a dynamic platform for blood collection in a country like Nepal and can be considered for implementation for NEQAS for HIV testing. DOI: http://dx.doi.org/10.3126/saarctb.v8i2.5897 SAARCTB 2011; 8(2): 23-27